TEKNOLOGI SISTEM INTEGRASI TERNAK, TANAMAN, DAN IKAN PADA LAHAN PEKARANGAN DAN TEKNOLOGI PENGOLAHAN BAHAN MAKANAN GUNA PENINGKATAN PENDAPATAN KELUARGA DI DESA CANGKRINGTURI, SIDOARJO - Sukarjati Sukarjati; Tatang Sopandi; Pungky Slamet WK (LPPM Universitas PGRI Adi Buana Surabaya, 2017)
Objective of KKN-PPM is to overcome the problems encountered in the village Cakringturi that the low incomes, lack of knowledge and understanding of environmental management, especially land yard. The solution to solve the problem is to empower rural communities through land use courtyard with technology integration system of livestock, crops and fish and provide food processing technology skills.Methods: Counseling, Mentoring, Training. Result: K1 program: Land yard citizens have been utilized, Product Probiofish, Aquaponics, Raising catfish in the pond Bis, The Carambola Fruit Cultivation along the river, Product instant and syrup TOGA, Vertikultur. K2 program: Competition Fun Cake in early childhood, Competition Beuty and Hijab Class, Teaching in Early Childhood Educatio. K3 Program : : Tutoring for elementary school children, Work with the community service, Yasinan, tahlilan, & diba'an, Assist Posyandu services. Distribution of poor rice, Visits to polindes,, Decorating in early childhood classrooms, Coordination with Karangtaruna, A visit to the village, Assist village. Conclusion: The entire planning of the program, both the main program, additional, or auxiliary implemented very well and smoothly by all students of KKN PPM 2015. Society and village and community leaders strongly support KKN PPM program and community empowerment have been successfully carried out. Keywords : Community EmpowermentCatfish in the pond bis, Aquaponics, Vertikultur, Star fruit cultivation, Instant and Syrup Toga.